Aplikasi Rehabilitasi dan Terapi Tangan untuk Pasien Stroke dengan menggunakan Kinect - Max Christian; Liliana Liliana; Iwan Njoto Sandjaja (Jurnal Infra, 2017)
Stroke is one of the most common cause of death after heart disease and cancer. Stroke occurs when an artery to the brain is blocked. Lots of things may cause stroke to different people, some of them are smoking, high blood pressures and sickle cells. One of the common kind of stroke is hemiplegia which makes the person who suffers from it loses the ability to move half of their body parts.For a person that suffer stroke to reavh full or almost full recovery, a continuos rehabilitation is needed. It can be both psychology and physical rehabilitation. But since they have to go to a hospital or a rehabilitation centre to get rehabilitation, it makes them hard to receive proper treatment and theraphy. With Kinect, a home rehabilitation therapy for stroke patients is possible, with less cost and more efficient than going to a hospital or hiring a private therapist.Kinect is a camera with depth sensor that is released by Microsoft primarily for XBOX 360, but then people start developing computer applications with Kinect, so nowadays there’s a lot of use of Kinect if paired up with computers. With Unity which is a game development software, an application for that particular home rehabilitation can be made. It will feature one kind of a 3 dimensional model but simple activity that hopefuly can help improve storke patients’ conditions. It would make them rasie their hand to do the activity in the application which would train them to use their hands again after suffering from stroke.